Pengaruh Penggunaan Kangkung (Ipomoea aquatica) Afkir dan Ampas Tahu Terfermentasi terhadap Performan dan IOFC Ternak Babi Peranakan Landrace Fase Grower-Finisher - Riu, Konsolatrix Voni; Dodu, Togu; Nenobais, Mariana (Yayasan Sumber Daya Manusia Cerdas, 2024)
The aim of this research was to determine the effect of using rejected kale (Ipomoea aquatica) and fermented tofu dregs in rations on the performance and IOFC (Income Over Feed Cost) of grower-finisher landrace pigs. This research was conducted at the Manoneh Pig Farm, Naioni Village, Alak District, Kupang City. The material used was 12 landrace pigs, aged 3-4 months, initial body weight was 30.00 – 49.00 kg with an average of 41.25 kg (CV = 15.48%). The experimental method used was a randomized block design (RBD) with 4 treatments and 3 replications. The treatments tested were R0: rations without a mixture of rejected kale and fermented tofu dregs, R1: rations containing 10% mixture of rejected kale and fermented tofu dregs, R2: rations containing 15% mixture of rejected kale and fermented tofu dregs, R3: rations containing 20% a mixture of rejected kale and fermented tofu dregs. The variables studied were performance consisting of ration consumption, body weight gain and ration conversion and IOFC. The collected data were analyzed using analysis of variance (ANOVA). The results of the analysis of variance showed that the use of rejected kale and fermented tofu dregs in the ration had a significant effect (P<0.05) on body weight gain, ration conversion and IOFC, but had no significant effect (P>0.05) on ration consumption. It was concluded that the ration using rejected kale and fermented tofu dregs at levels of 10%, 15%, and 20% had relatively the same effect on ration consumption, improving ration conversion, increasing body weight gain and IOFC.